What Makes Young People Think Positively About Social Distancing During the Corona Crisis in Germany? - Rieger, Marc Oliver (Frontiers in Sociology, 2020)
In a survey among 250 subjects recruited at a German university and predominantly university students, we elicit opinions about social distancing, i.e. the necessity to keep away from other people to slow down the speed of the ongoing SARS-CoV2 epidemics. The good news is that most students are supportive to it. A minority, however, does not completely agree. We find that how many elderly persons subjects knew personally, was the most significant factor for their attitudes towards social distancing. We also found a significant negative impact of believe in conspiracy theories on these attitudes. These theories have a non-negligible number of proponents, even among university students. Moreover, a certain degree of mistrust to media is widespread (around a third of the subjects). To improve positive attitudes to social distancing and thus to improve compliance we recommend therefore to emphasize relations of persons to elderly people in health communications more and to continue fighting against fake news and conspiracy theories regarding SARS-CoV2.